Synthesis of Flower-Like AgI/BiOCOOH p-n Heterojunctions With Enhanced Visible-Light Photocatalytic Performance for the Removal of Toxic Pollutants - Li, Shijie; Jiang, Wei; Xu, Kaibing; Hu, Shiwei; Liu, Yu; Zhou, Yingtang; Liu, Jianshe (Frontiers in Chemistry, 2018)
In this study, flower-like AgI/BiOCOOH heterojunctions were constructed through a two-step procedure involving the solvothermal synthesis of BiOCOOH microflowers followed by AgI modification using a precipitation method. These novel photocatalysts were systematically examined by XRD, UV−vis DRS, SEM, TEM, EDS, and PL spectroscopy techniques. The AgI/BiOCOOH heterojunction were studied as a decent photocatalyst for the removal of the industrial dye (rhodamine B, and methyl blue) and antibiotic (tetracycline) under visible light. The AgI/BiOCOOH heterojunctions are much more active than bare BiOCOOH, and AgI, which could be ascribed to the improved separation of charge carriers, resulting from the formation of p-n heterojunction between two constituents. The holes and •O2– were detected as the main active species responsible for the pollutant degradation. The results showed that a highly efficient visible-light-driven photocatalytic system was developed for the decomposition of toxic pollutants.